(3HZjI GdWGdH aj eYQaI GdeaQhV hGdhGLHs - (3GdMdj, GdLfGLj, GdfLaj, ef Bd cGTa GdZWGA, LYaQ Hf NVQ Hf TdGd, J (B1227 (3g`s ((3eMeO Hf OQhjTs)
(3ChdgG (B:s
(3YHKG hCfce EdjfG dG JQLYhf(B. (3acGf Pdc dZQV heUdMI hdjS Pdc GdZQV YGFOG Edjg dJfRjgg Yf GdGMJjGL Edi TjA(B...s
(3BNQgG (B:s
(3aj GdMVQ CYGO hbVi eWdbG hef CJe (B... (3fGSjG CYGO aj GdhbJ dG aj NGQLgs
(3JHUQI GdeDda (B:s
(3aj SfI haGJg GNJdGa(B: 1228(3, h(B: 1227(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: (3L(B1(3, U(B491s
(3GdCYdGe(B: (3L(B2(3, U(B124s
(3eYLe GdeDdajf(B: (3L(B1(3, U(B491s
Keywords: (3abg GdePGgH GdCNQis